(untitled) (Bangladesh Journal of Medical Physics, 2025)
Triple negative breast cancer is an aggressive malignancy lacking targeted therapies. To uncover new therapeutic strategies, we analyzed RNA- Seq data from nine paired TNBC and adjacent normal tissues. We identified 2,329 differentially expressed genes, with 1,012 upregulated and 1,317 downregulated. Upregulated transcripts such as BIRC5, CDC20, and XRCC2 were strongly enriched in cell cycle progression, DNA repair, and mitotic regulation, consistent with the hyperproliferative nature of TNBC. Conversely, reduced expression of EGR3, SOCS2, SLC7A2, NLGN1, and NTRK2 indicated suppression of cytokine-mediated signaling, immune regulation, and neurotrophin-related pathways, reflecting immune evasion and loss of differentiation cues. Network analysis pinpointed BIRC5 and AURKA as key hub genes. Structure-based screening of FDA-approved compounds revealed nebivolol, a β₁-adrenergic blocker, as a potential inhibitor of both proteins. Collectively, our findings reveal a dual transcriptomic strategy in TNBC, characterized by the activation of proliferative programs alongside suppression of immune-related pathways. Through integrative in silico analyses, we identify nebivolol as a potential repurposed therapeutic candidate. However, these results are computational and hypothesis-generating in nature, requiring rigorous experimental and clinical validation before any translational application. Ban. J. Med. Phys., Vol -16, Issue -2, 2025 : 56-64